ANALISIS PENGARUH OVERCLOCKING PADA PROCESSOR TERHADAP KINERJA SISTEM - Imran Rahmat; Dedy Irfan; Zulhendra Zulhendra (Universitas Negeri Padang, 2014)
This research aims to gain a significant performance speed processor after the processor clockspeed increase in learning the principles of good processor clockspeed increase , as well as the stable and see the effect caused by overclocking the computer system performance when used daily . This research is an experiment that is true experiment , data collection technique is to conduct experiments and take measurements on the processor . Data analysis technique used is to look at the percentage increase in performance by comparing the measurement results with the end of the initial measurement . The measurement results showed that successful overclock to 17 % with the processor fan is still the standard and performance of the system is still stable , which is indicated by the results of measurements of OCCT . The results of measurements of sintetic test shows that the system performance is also increasing the speed increases . So also with the results of measurements and timing test rendering test . Real - life test also showed when the game GTA IV and the blender running, not the case of failure , such as crashes and down .